PENGARUH LEAFLET TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN HIPERTENSI DI PUSKESMAS MARTAPURA 1 - Esty Restiana Rusida; Siti Hamdah; Cast Torizellia (Universitas Borneo Lestari, 2024)
The high mortality caused by hypertension continues to increase every year, this is due to the absence of symptoms that arise. A person develops hypertension if blood pressure exceeds 140/90 mmHg. One of the treatments for hypertension is adherence to treatment, because compliance is one of the keys to the success of therapy. Treatment adherence can be improved by being given leaflets. The purpose of this study was to determine the effect of leaflets and the level of compliance of hypertensive patients at the Martapura 1 Health Center. This research method is pre-experimental with One Group Pretest and Posttest Design design. The total sample in this study was 220 respondents. Sampling by filling out the Morisky Medication Adherence Scale-8 questionnaire. Based on the pretest results, high compliance was 23 people (10.5%), medium compliance was 66 people (30.0%), and low compliance was 131 people (59.5%). The posttest results obtained high compliance of 120 people (54.5%), medium compliance of 90 people (40.9%), and low compliance of 10 people (4.5%). Data analysis using the McNemar test showed a significant effect with p-value = 0.000 (p<0.05), so it can be concluded that there is an effect of giving medication adherence leaflets at the Martapura 1 Health Center.